VALIDASI E-BOOK INTERAKTIF BERBASIS KEARIFAN LOKAL PADA PEMBELAJARAN IPAS KELAS IV DI UPT SD NEGERI SIDOREJO 1 - Siti Nurhalimah; Ina Agustin; Sri Cacik (PT. Hasba Edukasi Mandiri, 2026)
This study was conducted to determine the feasibility of an interactive e-book incorporating Semanding local wisdom for Science and Social Studies (IPAS) learning in fourth-grade elementary school classes. The research was motivated by the limited availability of contextual digital learning media and the insufficient integration of local wisdom into IPAS instruction at the elementary school level. The study employed a Research and Development (R&D) approach using the ADDIE model, with particular emphasis on the development phase and product validation process. The product was evaluated by three validators consisting of a media expert, a language expert, and a subject-matter expert. The validation instrument assessed several aspects, including visual appearance, functionality, content, language, and curriculum alignment. Data were analyzed using percentage calculations to determine the feasibility level of the developed media. The findings revealed that the interactive e-book achieved a validation score of 100% from the media expert, 96% from the language expert, and 85% from the material expert, resulting in an overall average score of 93.67%, which falls within the very feasible category. These results indicate that the developed media satisfies the required feasibility standards in terms of design, functionality, language use, and content quality. Therefore, the interactive e-book based on Semanding local wisdom is considered highly appropriate for use as a learning medium in fourth-grade IPAS learning and is ready to be implemented during the product trial stage.